The Role of Digital Advertising in the 2024 Indonesian Presidential Election - Muhammad Maulana; Inas Hamdan Billah; Muhammad Fathier Alkahfie; Akhirul Aminulloh (Cakra Communico: Journal of Communication Science, 2024)
Advertising is one of the strategies widely used by companies in promoting their products or services to the public. The functions of advertising are to provide information that makes consumers aware of a brand, persuade consumers to try the advertised product or service, maintain consumer memory of the advertised product or service, as an added value to the advertised product, and as a companion to efforts made by the company in terms of promotion. In the rapid development of technology, this also affects the advertising strategies carried out, one of which is by using mass media, such as television, radio, magazines and newspapers. Mass media itself comes from the word media, which is a tool or means used to convey from communicators to audiences while "mass" refers to a formless collectivity, whose components are difficult to distinguish messages from one another. There are also six perspectives in terms of seeing the role of mass media, namely as a means of learning to know various events, a mirror of various events in society and the world, which reflects what it is, as a filter or gatekeeper that selects various things, as a guide in presenting various information and ideas to the audience, and as an interlocutor or partner so that interactive communication occurs. The use of mass media in advertising has its own function and is considered more effective because it can reach a larger audience so that messages or advertisements carried out are more effective on marketing targets, build brand image, increase brand awareness, and even influence consumer behavior in purchasing a product.